2016
DOI: 10.1371/journal.pmed.1002055
|View full text |Cite
|
Sign up to set email alerts
|

South Asia as a Reservoir for the Global Spread of Ciprofloxacin-Resistant Shigella sonnei: A Cross-Sectional Study

Abstract: BackgroundAntimicrobial resistance is a major issue in the Shigellae, particularly as a specific multidrug-resistant (MDR) lineage of Shigella sonnei (lineage III) is becoming globally dominant. Ciprofloxacin is a recommended treatment for Shigella infections. However, ciprofloxacin-resistant S. sonnei are being increasingly isolated in Asia and sporadically reported on other continents. We hypothesized that Asia is a primary hub for the recent international spread of ciprofloxacin-resistant S. sonnei.Methods … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
70
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(78 citation statements)
references
References 30 publications
(40 reference statements)
7
70
0
1
Order By: Relevance
“…South Asia has been shown to serve as a hub for dissemination of FQ-resistant S. sonnei clones around the globe (20), and our data suggest that the CA FQ-resistant SFr population also originated from the South Asian clade. Considering that no patients from the SFr outbreak cluster reported international travel (16), the introduced resistant clone could have been circulating locally prior to involvement in the outbreak.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…South Asia has been shown to serve as a hub for dissemination of FQ-resistant S. sonnei clones around the globe (20), and our data suggest that the CA FQ-resistant SFr population also originated from the South Asian clade. Considering that no patients from the SFr outbreak cluster reported international travel (16), the introduced resistant clone could have been circulating locally prior to involvement in the outbreak.…”
Section: Discussionmentioning
confidence: 54%
“…The genomes of CA S. sonnei isolates were compared with the genomes of global S. sonnei clones reported by previous studies (see Data Set S1, sheet 2, in the supplemental material) (1921) using genome-wide SNP analysis. The isolates from the aforementioned studies (188 total) were selected based on following criteria: (i) to represent all lineages as per Holt et al (19), (ii) different clades described by authors (Global III, Central Asia III), and (iii) various ciprofloxacin resistance mutations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, military personnel and other travelers from high-resource countries who visit these endemic settings are also at risk for acquiring Shigella infections and disseminating them upon returning home. The global spread of multidrug-resistant Shigella has been traced to the wide dissemination of single clones (7), and this ease of transmission threatens the ability to treat shigellosis with antibiotics that are effective, readily available, and affordable. Because of the limitations of current efforts to control the spread of Shigella, development of a Shigella vaccine is considered a public health priority.…”
mentioning
confidence: 99%
“…Our previous work demonstrated that all cipR S. sonnei globally were clonal and emerged once from a single lineage that likely arose in South Asia 22 . Here, we describe the expansion of a single lineage III clade of cipR S. sonnei by providing phylo-temporal insights into its extant clonal dynamics using clinical samples obtained from children admitted to three paediatric facilities in Ho Chi Minh City (HCMC) between 2014 and 2016.…”
Section: Introductionmentioning
confidence: 99%